Integrating seismic refraction and electrical approaches in determining geophysical properties of near-surface cavities in Calabar-Ikom highway, Odukpani, Cross River State, Nigeria - Ukorebi Asuquo , Bassey; M. George , Anthony; Akaerue , Emmanuel; Chigoziem Akakuru , Obinna (International Journal of Advanced Geosciences, 2024)
Integrated seismic refraction tomography (SRT) and electrical resistivity tomography (ERT) were used to study near-surface cavities with the aim of determining their geophysical properties. Five seismic refraction profiles around the study area were carried out using a 24-channel seismograph (ES-3000) while four ERT and ERT profiles were also conducted with IGIS resistivity meter and PLOTREFA software respectively. The data was processed using the RES2DINV software. Travel-time curves and velocity models were generated from the processed SRT data for each survey line, and 2-D inverted apparent resistivity models along the same lines were also generated for the purpose of comparison respectively. The results as obtained from the profiles showed SRT 1 (with a modelled velocity of 1,216 m/s in layer two at a depth of approximately 11 m - 20 m beneath the subsurface and an estimated cavity diameter of 11 m) and ERT 1 (with an apparent resistivity of approximately 826 Ωm and a depth of approximately 12.5 m – 16 m) indicates that the near-surface cavity outcrop links with a close-by mountainous structure in the EW direction. Profiles SRT 2 (with an approximately modeled velocity layer of 980 m/s in layer two at an approximate depth of 3.5 m – 7.0 m) and SRT 3 (with a modeled velocity layer of approx. 1,000 m/s in layer two at an approximate depth of 4.0 m – 7.0 m and 3.0 m – 9.0 m); ERT 2 (with an apparent resistivity of approximately 80 Ωm); and ERT 3 (with apparent resistivities of 116 Ωm and 182 Ωm at depths of approximately 3.5 m to 6.4 m and 4.0 m to 15.8 m) indicates that the surface cavity outcrop extends underneath the road network (Odukpani Central Section of Calabar-Ikom Highway) with a width of approximately 12 m. Profiles SRT 4 and SRT 5 (with an average velocity layer of 1,000 m/s in layer two at an approximate depth of 6.0 m – 13.2 m), and ERT 4 (with apparent resistivity ranging between 121 Ωm and 172 Ωm) at a depth of approximately 9.5 m to 20.0 m reveal that the near-surface cavity extends up to about 11 m across the highway and about 120 m away from the edge of the road. The above result will serve as reliable technical information to Transport and Building Construction Engineers on the presence of cavities along road networks and settlement areas in Odukpani Local Government Area. The recommendation is also made for the use of other geophysical techniques like Ground Penetration Radar (GPR) in conjunction with SRT and ERT to get higher-resolution imagery of the study area.